Transforming big data into knowledge: the role of knowledge management practice. Issue 8 (12th September 2019) - Chierici, Roberto; Mazzucchelli, Alice; Garcia-Perez, Alexeis; Vrontis, Demetris
Abstract : Purpose: The purpose of this paper is to empirically investigate how big data collected from social media contribute to knowledge management practices, innovation processes and business performance. Design/methodology/approach: The study used 418 questionnaires collected from firms that actively invest in marketing, advertising and communication in the Italian market. The hypotheses testing and analysis were conducted using structural equation modeling. Findings: The results reveal that customers' data gathered from social media produce different effects on knowledge management practices and firms' innovation capacity. Furthermore, increased innovation capacity turned out to affect customer relationship performance directly, while it contributes to gain better financial performance only when it is used to gain relational outcomes. Originality/value: The outcomes of the study help firms to develop a clear understanding about which big data retrieved from social media can be useful to improve their knowledge management practices and enhance their innovation capacity. Moreover, by investigating the mediating role of big data knowledge management in the context of social media knowledge acquisition and innovation capacity, this study also extends the mediation variables used to understand the relationship between knowledge capabilities and practices and innovation constructs.